Asuhan Keperawatan Penerapan Terapi Musik Klasik Pada Lansia Hipertensi dengan Gangguan Pola Tidur - Shabilla Putri Wahyuni; Fitri Afdhal; Erik Rosadi; Ria Wulandari (JURNAL KESEHATAN TERAPAN, 2026)
Hypertension is a degenerative disease frequently experienced by the elderly and is closely linked to sleep disturbances. Sleep disturbances can worsen health conditions and reduce quality of life. Classical music therapy, as a non-pharmacological intervention, is considered effective, affordable, and safe for improving sleep quality. The purpose of this study was to determine the application of classical music therapy to elderly hypertensive patients with sleep disturbances at Bhayangkara Mohamad Hasan Hospital, Palembang, in 2025. This study used a case study design with two elderly subjects with stage I hypertension experiencing sleep disturbances. Classical music therapy was administered for three consecutive days, 30–60 minutes before bedtime. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). The results showed improved sleep quality in both patients, with a decrease in PSQI scores from 8 to 4 in the first patient and from 7 to 3 in the second patient. This therapy also lowered blood pressure, reduced headache complaints, and increased relaxation and comfort. Conclusion: Classical music therapy is effective as a non-pharmacological intervention to improve sleep quality in elderly hypertensive patients and can be incorporated into geriatric nursing interventions